Resolving Non‐Specific and Specific Adhesive Interactions of Catechols at Solid/Liquid Interfaces at the Molecular Scale. Issue 33 (4th July 2016) - Utzig, Thomas; Stock, Philipp; Valtiner, Markus
Abstract: The adhesive system of mussels evolved into a powerful and adaptive system with affinity to a wide range of surfaces. It is widely known that thereby 3, 4‐dihydroxyphenylalanine (Dopa) plays a central role. However underlying binding energies remain unknown at the single molecular scale. Here, we use single‐molecule force spectroscopy to estimate binding energies of single catechols with a large range of opposing chemical functionalities. Our data demonstrate significant interactions of Dopa with all functionalities, yet most interactions fall within the medium–strong range of 10–20  k B T . Only bidentate binding to TiO2 surfaces exhibits a higher binding energy of 29  k B T . Our data also demonstrate at the single‐molecule level that oxidized Dopa and amines exhibit interaction energies in the range of covalent bonds, confirming the important role of Dopa for cross‐linking in the bulk mussel adhesive. We anticipate that our approach and data will further advance the understanding of biologic and technologic adhesives. Abstract : Biophysics : Dopa–surface interactions are very important for nanotechnology and surface modification (Dopa=3, 4‐dihydroxyphenylalanine). The binding energies between Dopa and various surfaces were determined by single‐molecule force spectroscopy (see picture; Δ G =free energy and F =force).